Bone Mineral Density in Adults With Congenital Adrenal Hyperplasia: A Systematic Review and Meta-Analysis - Rangaswamaiah, Swetha; Gangathimmaiah, Vinay; Nordenstrom, Anna; Falhammar, Henrik (Frontiers in Endocrinology, 2020)
Background: Decreased bone mineral density (BMD) is a concern in patients with Congenital Adrenal Hyperplasia (CAH) due to lifelong glucocorticoid replacement. Studies till date have yielded conflicting results. We wanted to systematically evaluate the available evidence regarding BMD in adult patients with CAH. Methods: We searched Medline, Embase and Cochrane Central Register of Controlled Trials to identify eligible studies. Studies comparing BMD in CAH patients with age- and sex-matched controls were included. Age less than 16 years and absence of controls were exclusion criteria. Two authors independently reviewed abstracts, read full-text articles, extracted data, assessed risk of bias using Newcastle-Ottawa scale and determined level of evidence using Grading of Recommendations Assessment, Development and Evaluation methodology. Results: Nine case-control studies with a total sample size of 598 (cases n=254, controls n=344) met eligibility criteria. Total body BMD (Mean Difference [MD]-0.06; 95%CI -0.07, -0.04), lumbar spine BMD (MD -0.05; 95%CI -0.07, -0.03) and femoral neck BMD (MD -0.07; 95%CI -0.10, -0.05) was lower in cases compared to controls. Lumbar spine T-scores (MD -0.86; 95%CI -1.16, -0.56) and Z-scores (MD -0.66; 95%CI -0.99, -0.32) and femoral neck T-scores (MD -0.75 95%CI -0.95, -0.56) and Z-scores (MD -0.27 95%CI -0.58, 0.04) were also lower in cases compared to controls. No clear correlation between BMD and glucocorticoid dose was found. Conclusion: BMD in adult patients with CAH was lower compared to controls. Although no clear dose-response relationship between glucocorticoid dose and BMD was found, it would be prudent to avoid over-treatment with glucocorticoids.